Preparation method of DL-methionine bulk crystals

By using the binary growth regulator EDTA-SDS to control crystal growth, DL-methionine block crystals with excellent thickness and bulk density were prepared, solving the problems of poor morphology and low bulk density in the prior art and making it suitable for industrial production.

CN120623085APending Publication Date: 2025-09-12TIANJIN UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510785369.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2025-04-10
Filing Date
2025-06-12
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The existing DL-methionine crystal morphology is poor and the bulk density is low, making it difficult to reach the ideal level. In addition, there is a gap between domestic technology and foreign advanced technology.

Method used

DL-methionine bulk crystals were prepared by using a binary growth regulator EDTA-SDS by controlling the stirring rate, temperature and cooling rate. EDTA inhibited the growth of crystal faces, while SDS promoted the growth of crystal thickness.

Benefits of technology

DL-methionine block crystals with a thickness of up to 260 μm and a bulk density of up to 0.77 g/mL were prepared with good morphology, which are suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120623085A_ABST
    Figure CN120623085A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a DL-methionine bulk crystal. The preparation method comprises the following steps: under a stirring condition, heating a mixed solution of a DL-methionine raw material and a binary growth regulator to 40-60 DEG C, keeping the temperature for 30-120 minutes, then cooling to 10-30 DEG C, and keeping the temperature for 10-60 minutes to obtain the DL-methionine bulk crystals. The specific binary growth regulator is adopted and matched with the slow cooling crystallization process, the obtained methionine crystals are blocky crystals, the thickness can reach 260 microns, the bulk density can reach 0.77 g / mL, subsequent further production and application are facilitated, in addition, the technological process is simple, raw materials are easy to obtain, and industrial large-scale production and application are facilitated.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of chemical engineering industrial crystallization, and particularly relates to a method for preparing DL-methionine block crystals. Background Art

[0002] DL-methionine, also known as DL-methionine, has a CAS number of 59-51-8 and a molecular formula of C5H 11 NO2S, with a molecular weight of 149.21, is the only essential amino acid in living organisms that contains a thioether group. It has a slightly sweet taste and generally appears as white flaky crystals or crystalline powder. It is easily soluble in water, slightly soluble in methanol and ethanol, and poorly soluble in non-polar solvents such as chloroform and ether. Its density is 1.340 g / cm 3 , with a decomposition temperature of approximately 281°C. DL-methionine is a typical racemic compound, composed of equal amounts of D-methionine and L-methionine. The two molecules are enantiomers, exhibiting mirror-symmetry in their spatial structures and possessing opposite chirality. DL-methionine is commonly used in numerous industries, including feed, food, and medicine. It is particularly useful as a feed additive. While ensuring the nutritional needs of poultry, it not only reduces reliance on expensive protein raw materials and significantly lowers feed costs, but also significantly increases egg production and improves egg quality.

[0003] The currently widely used method is to first prepare DL-methionine metal salts through an organic synthesis reaction, followed by a neutralization reaction to induce the product to precipitate in the form of crystals. After treatment and recrystallization, the final product is usually in the form of flakes or crystalline powder. However, this form has obvious drawbacks. Due to its poor morphology, the bulk density is as low as 0.3 g / mL, and the yield is difficult to achieve the ideal level. More seriously, the domestic DL-methionine preparation technology lags behind advanced foreign technologies, putting it at a disadvantage in the international market competition.

[0004] Therefore, finding a method for preparing DL-methionine bulk crystals with simple process, good morphology and high bulk density remains a very challenging problem. Summary of the Invention

[0005] In order to solve the current problems of DL-methionine crystal morphology defects and low bulk density, the present application provides a method for preparing DL-methionine bulk crystals by adding a binary growth regulator EDTA-SDS. The process flow is simple, and the prepared DL-methionine has good morphology and high bulk density.

[0006] One of the purposes of the present application is to provide a method for preparing DL-methionine bulk crystals, comprising the following steps: Under stirring conditions, the mixed solution of the DL-methionine raw material and the binary growth regulator is heated to 40-60°C (for example, 40°C, 42°C, 45°C, 47°C, 50°C, 52°C, 55°C, 58°C, 60°C, etc.) and maintained for 30-120 min (for example, 30 min, 40 min, 50 min, 60 min, 70 min, 80 min, 90 min, 100 min, 110 min, 120 min, etc.), and then cooled to 10-30°C (for example, 10°C, 12°C, 15°C, 17°C, 20°C, 22°C, 25°C, 27°C, 30°C, etc.) and maintained for 10-60 min (for example, 10 min, 15 min, 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min, etc.) to obtain DL-methionine block crystals.

[0007] Preferably, the stirring rate is 200-300 r / min, for example, 200 r / min, 210 r / min, 220 r / min, 230 r / min, 240 r / min, 250 r / min, 260 r / min, 270 r / min, 280 r / min, 290 r / min, 300 r / min, etc.

[0008] Preferably, the binary growth regulator is a combination of ethylenediaminetetraacetic acid (EDTA) and sodium dodecyl sulfate (SDS). Preferably, the mass ratio of EDTA to SLS is (5-9):1, such as 5:1, 6:1, 7:1, 8:1, 9:1, etc.

[0009] In this application, in a pure water system, DL-methionine generally presents hexagonal flakes, with poor crystal habit morphology and low bulk density. Although the crystal habit and polymorphism of DL-methionine have been widely studied, the most common method is to add additives to achieve the desired control. However, the bulk density under existing methods is still not ideal, and can only reach about 0.6 g / mL at most. The carboxyl groups of EDTA can form hydrogen bonds with the hydrogen bond acceptors and donors on the (002) and (011) crystal faces of the crystal, hindering the attachment of solute molecules to the crystal faces and resulting in strong inhibition of crystal face growth. In contrast, the absolute value of the binding energy of SDS with these two crystal faces is significantly lower than that of EDTA, indicating that SDS has a weaker adsorption effect on the crystal faces and a lower probability of contact with the crystal faces. Therefore, in a system where EDTA and SDS coexist, EDTA's inhibitory effect on crystal face growth dominates. Although SDS has limited adsorption capacity, it has a significant promoting effect on crystal growth in the width direction, making it play a unique role in crystal growth. The addition of a small amount of SDS does not hinder the contact between the solute and the crystal face due to steric hindrance. Instead, it can strip the solvent layer on the crystal surface, which helps the solute reach the growth site, promotes crystal growth, and reduces the inhibitory effect of EDTA on this crystal face, thereby affecting the aspect ratio of the crystal. In addition, when the growth rate of the (002) and (011) crystal faces decreases, more supersaturation will be used for the growth of the (100) crystal face, which helps to increase the thickness of the crystal. This binary growth regulator EDTA-SDS is of great significance for controlling the morphology and size of crystals by finely regulating the growth rate of different crystal faces.

[0010] Preferably, in the mixed solution of the DL-methionine raw material and the binary growth regulator, the concentration of the binary growth regulator is 200-800 ppm (e.g., 200 ppm, 300 ppm, 400 ppm, 500 ppm, 600 ppm, 700 ppm, 800 ppm, etc.), and the concentration of the DL-methionine raw material is 3-7wt%, e.g., 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, etc.

[0011] Preferably, the cooling rate is 0.03-0.1°C / min, for example, 0.03°C / min, 0.04°C / min, 0.05°C / min, 0.06°C / min, 0.07°C / min, 0.08°C / min, 0.09°C / min, 0.1°C / min, etc.

[0012] Preferably, the preparation method further comprises sequentially performing solid-liquid separation and drying on the mixture obtained after cooling and maintaining.

[0013] Preferably, the solid-liquid separation is carried out by filtration.

[0014] Preferably, the drying temperature is 40-50°C (e.g., 40°C, 42°C, 45°C, 48°C, 50°C, etc.), and the drying time is 12-48 h (e.g., 12 h, 15 h, 18 h, 24 h, 30 h, 36 h, 40 h, 42 h, 45 h, 48 h, etc.).

[0015] A second object of the present invention is to provide a preparation method according to the first object to prepare DL-methionine block crystals.

[0016] Preferably, the methionine crystals are block-shaped with a thickness of up to 260 μm and a bulk density of up to 0.77 g / mL.

[0017] This application has the following beneficial effects: This application uses a specific binary growth regulator in combination with a slow cooling crystallization process. Not only can the obtained methionine crystals be block crystals with a thickness of up to 260 μm and a bulk density of up to 0.77 g / mL, which are convenient for subsequent production applications, but the process is also simple and the raw materials are readily available, making it easy for industrial large-scale production and application. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 These are scanning electron microscope images of the DL-methionine crystals obtained in Comparative Examples 1-3, when no growth regulator is present, only SDS is present, or only EDTA is present. The scale is 250 μm. Figure 2 This is a scanning electron microscope image of the DL-methionine crystals finally obtained in Example 1 in the presence of a binary growth regulator (EDTA+SDS) (EDTA:SDS=7:1), with a scale of 500 μm. DETAILED DESCRIPTION

[0019] The technical solution of the present invention is further described below by way of specific embodiments. It should be understood by those skilled in the art that the embodiments are merely to help understand the screening process of the optimal conditions in the present invention and should not be regarded as specific limitations of the present invention.

[0020] Example 1: (1) Weigh 5 g of DL-methionine and add it to a jacketed crystallizer filled with 100 g of water. Add the binary growth regulator EDTA-SDS to a concentration of 400 ppm, where the mass ratio of EDTA to SDS in the binary growth regulator is 7:1. (2) Set the stirring blade speed to 250 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 50 °C, and keep it constant for 1 hour to ensure that the DL-methionine solid and growth regulator are completely dissolved; (3) Cool down to 20°C at a rate of 0.05°C / min and keep the temperature constant for 30 min to grow crystals; (4) Filter the crystalline product and place it in a vacuum drying oven at 40 °C for 36 h.

[0021] The DL-methionine crystal product prepared in Example 1 was subjected to scanning electron microscope image test (eg Figure 2 The product was found to be block-shaped with a thickness of approximately 250 μm.

[0022] The bulk density of the DL-methionine crystal product prepared in Example 1 was tested, and the result was 0.67 g / mL.

[0023] Example 2: The only difference from Example 1 is that the concentration of the binary growth regulator is 800 ppm.

[0024] The DL-methionine crystal product obtained in Example 1 was subjected to the same test as in Example 1, and it was found that the final product was in block form, with a thickness of about 260 μm and a bulk density of 0.77 g / mL.

[0025] Example 3: (1) Weigh 7 g of DL-methionine and add it to a jacketed crystallizer filled with 100 g of water. Add the binary growth regulator EDTA-SDS to a concentration of 600 ppm, where the mass ratio of EDTA to SDS in the binary growth regulator is 5:1. (2) Set the stirring speed to 300 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 40 °C, and keep it constant for 120 minutes to ensure that the DL-methionine solid and growth regulator are completely dissolved; (3) Cool down to 10°C at a rate of 0.03°C / min and keep the temperature constant for 60 min to grow crystals; (4) Filter the crystal product and place it in a vacuum drying oven at 50°C for drying.

[0026] The DL-methionine crystal product obtained in Example 1 was subjected to the same test as in Example 1, and it was found that the final product was in block form, with a thickness of about 210 μm and a bulk density of 0.63 g / mL.

[0027] Example 4: (1) Weigh 3 g of DL-methionine and add it to a jacketed crystallizer filled with 100 g of water. Add the binary growth regulator EDTA-SDS to a concentration of 200 ppm, where the mass ratio of EDTA to SDS in the binary growth regulator is 9:1. (2) Set the stirring speed to 200 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 60 °C, and keep it constant for 30 minutes to ensure that the DL-methionine solid and growth regulator are completely dissolved; (3) Cool down to 30°C at a rate of 0.1°C / min and keep the temperature constant for 10 min to grow the crystal; (4) Filter the crystalline product and place it in a vacuum drying oven at 45 °C for 48 h.

[0028] The DL-methionine crystal product obtained in Example 1 was subjected to the same test as in Example 1, and it was found that the final product was in block form, with a thickness of about 190 μm and a bulk density of 0.60 g / mL.

[0029] By comparing Example 1 and Example 2, it can be seen that when the concentration of the binary growth regulator increases, the inhibitory effect on the length and width directions becomes stronger, which is beneficial to the consumption of supersaturation in the thickness growth direction, increases the thickness of the crystal product, and further improves the product bulk density.

[0030] Comparative Example 1: (1) Weigh 5 g of DL-methionine and add it to a jacketed crystallizer containing 100 g of water without adding any growth regulator; (2) Set the stirring blade speed to 250 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 50 °C, and keep it constant for 1 hour to ensure that the DL-methionine solid is completely dissolved; (3) Cool down to 20°C at a rate of 0.05°C / min and keep the temperature constant for 30 min to grow crystals; (4) Filter the crystal product and place it in a vacuum drying oven at 40°C for drying.

[0031] Scanning electron microscope images of the product are shown in Figure 1 The obtained DL-methionine crystal product is in the form of spindle-shaped flakes with a bulk density of 0.33 g / mL.

[0032] Comparative Example 2: (1) Weigh 5 g of DL-methionine and add it to a jacketed crystallizer filled with 100 g of water. Add a single growth regulator, EDTA, at a concentration of 400 ppm. (2) Set the stirring blade speed to 250 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 50 °C, and keep it constant for 1 hour to ensure that the DL-methionine solid is completely dissolved; (3) Cool down to 20°C at a rate of 0.05°C / min and keep the temperature constant for 30 min to grow crystals; (4) Filter the crystal product and place it in a vacuum drying oven at 40°C for drying.

[0033] Scanning electron microscope images of the product are shown in Figure 1 The obtained DL-methionine crystal product is in the form of spindle-shaped flakes with a relatively high aspect ratio and a bulk density of 0.51 g / mL.

[0034] Comparative Example 3: (1) Weigh 5 g of DL-methionine and add it to a jacketed crystallizer filled with 100 g of water. Add a single growth regulator, SDS, at a concentration of 400 ppm. (2) Set the stirring blade speed to 250 r / min, use an intelligent constant temperature water bath ice machine to raise the temperature to 50 °C, and keep it constant for 1 hour to ensure that the DL-methionine solid is completely dissolved; (3) Cool down to 20°C at a rate of 0.05°C / min and keep the temperature constant for 30 min to grow crystals; (4) Filter the crystal product and place it in a vacuum drying oven at 40°C for drying.

[0035] Scanning electron microscope images of the product are shown in Figure 1 The obtained DL-methionine crystal product is in the form of thin flakes with a relatively low aspect ratio and a bulk density of 0.44 g / mL.

[0036] Comparative Example 4: The only difference from Example 1 is that the ratio of EDTA and SDS in the added binary growth regulator is 1:1.

[0037] The obtained DL-methionine crystal product was in the form of thin flakes and had a bulk density of 0.54 g / mL.

[0038] Comparative Example 5: The only difference from Example 1 is that the ratio of EDTA and SDS in the added binary growth regulator is 15:1.

[0039] The obtained DL-methionine crystal product was in the form of thin flakes and had a bulk density of 0.4 g / mL.

[0040] By comparing Example 1 with Comparative Examples 1-3, it can be seen that when no specific binary growth regulator is used, or when only any one of the binary growth regulators is used, the thickness of the obtained DL-methionine crystals does not change significantly or even decreases significantly, presenting a flake shape, and the bulk density remains at a relatively low level.

[0041] By comparing Example 1 and Comparative Examples 4-5, it can be seen that when the ratio between EDTA and SDS is within the range defined in this application, the thickness is greater and the bulk density is higher. At this time, the inhibitory effect of EDTA on crystal growth is dominant. After adding a small amount of SDS, the water molecules on the crystal surface can be stripped off, crystal growth is promoted, and the inhibitory effect of EDTA in the width direction is weakened, thereby achieving the optimal ratio for regulating the crystal morphology.

[0042] The present invention discloses and proposes a method for preparing DL-methionine bulk crystals. Those skilled in the art can, by referring to this patent, appropriately modify the ratio and concentration of the binary growth regulator, the cooling rate, and other conditions to achieve the goal of producing DL-methionine crystals with good morphology. The present invention has described the basic screening process for experimental conditions through certain examples. It is obvious that those skilled in the art can modify, alter, and combine the methods and products described herein without departing from the content, spirit, and scope of the present invention to implement the technology of the present invention. It is particularly important to note that all similar substitutions and modifications obvious to those skilled in the art are considered to be included in the spirit, scope, and content of the present invention.

Claims

1. A method for preparing DL-methionine bulk crystals, characterized in that The product has a very high bulk density, which is beneficial to the subsequent processing and production process. The preparation method includes the following steps: Under stirring conditions, the mixed solution of DL-methionine raw material and binary growth regulator is heated to 40-60°C and maintained for 30-120 minutes, and then cooled to 10-30°C and maintained for 10-60 minutes to obtain DL-methionine block crystals.

2. The preparation method according to claim 1, characterized in that The stirring rate is 200-300 r / min.

3. The preparation method according to claim 1, characterized in that The binary growth regulator is a combination of ethylenediaminetetraacetic acid and sodium lauryl sulfate.

4. The preparation method according to claim 3, characterized in that The mass ratio of the ethylenediaminetetraacetic acid and sodium lauryl sulfate is (5-9):

1.

5. The preparation method according to claim 1 or 3, characterized in that In the mixed solution of the DL-methionine raw material and the binary growth regulator, the concentration of the binary growth regulator is 200-800 ppm, and the concentration of the DL-methionine raw material is 3-7 wt %.

6. The preparation method according to claim 1, characterized in that The cooling rate is 0.03-0.1°C / min.

7. The preparation method according to claim 1, characterized in that The preparation method further comprises sequentially performing solid-liquid separation and drying on the mixture obtained after cooling and maintaining.

8. The preparation method according to claim 7, characterized in that The drying temperature is 40-50° C., and the drying time is 12-48 h.

9. DL-methionine block crystals are prepared according to the preparation method according to any one of claims 1 to 8.

10. The DL-methionine bulk crystals according to claim 9, characterized in that The thickness of the DL-methionine block crystals can reach 260 μm; The bulk density of the DL-methionine block crystals can reach 0.77 g / mL.